Pulmonary artery debanding in the cath lab: Lessons learned! - Zareef, Rana; Hassan, Sally Al; Younis, Nour; Tannoury, Theresia; Rassi, Issam El; Bitar, Fadi; Arabi, Mariam (Frontiers in Cardiovascular Medicine, 2022)
Background Although primary definitive repair of congenital heart disease has become the preferred management approach, pulmonary artery banding (PAB) remains a valuable palliative procedure used to restrict pulmonary blood flow in certain conditions. However, when the band is to be removed, another surgical intervention is usually required. Methods To describe percutaneous removal of pulmonary artery band, the medical records of patients who underwent this procedure were reviewed. Results Between 2000 and 2020, 143 patients underwent PAB. Of these, we attempted balloon debanding of the pulmonary artery in four patients. At the time of the procedure, the average age of patients was 36 ± 6.24 months, and their average weight was 12.37 kg. Band removal via catheter was successful in three cases and was associated with an adequate reduction in pressure gradient across the pulmonary artery band site (average of 71.67 ± 12.58 to 23.67 ± 2.89 mm Hg). None of the patients experienced complications during or after the procedure. Follow-up data after discharge (3–10 years) provides reassuring and satisfactory results. Conclusion Based on our findings, we suggest that percutaneous removal of the pulmonary artery band might be a safe and effective alternative to surgical debanding. However, studies with a larger sample are required for further clinical implementation of the technique.